ISSUES OF ATTRACTION OF FOREIGN INVESTMENTS IN THE ECONOMY (Conferencea, 2024)
The scientific thesis examines the theoretical and practical issues of attracting foreign investment. The issues of further development of the real sector of the economy by attracting foreign investment into the country's economy are analyzed. On the basis of research and analysis, the author's scientific conclusions are made.